PENERAPAN BAHAN TWEED PADA PEMBUATAN BUSANA READY TO WEAR - Febbry Dwiyanti Krisnayadi; Pipin Tresna Prihatin (Teknobuga, 2021)
Abstract. The purpose of this study was to 1) develop the writer's creativity in making ready to wear fashion using tweed material, and 2) apply the knowledge and skills gained during lectures, especially in fashion design and textile knowledge courses in ready to wear fashion products with using tweed material. The method used is the Project Based Learning (PBL) method. Supported by the study of literature is done by reading material in the form of books, articles and journals, or documents that are relevant to the problem under study. The results of the study are that ready to wear fashion brands have the opportunity to be developed into ready to wear clothing in Indonesia, because fashion processing using tweed material is rarely produced. In its use this tweed material can be used as ready to wear fashion and also used in parties. This ready to wear fashion with tweed material is proposed to target the market for teenage women to adults with age around 19-35 years. Rready to wear fashion by using tweed material can provide innovation to designers and the public in making a fashion product.